When too much closeness harms: circumflex artery injury during mitral valve surgery - Dumps, Christian; Simon, Philipp; Girdauskas, Evaldas; Girrbach, Felix (Frontiers in Cardiovascular Medicine, 2023)
Occlusion of the left coronary circumflex artery (LCX) during surgical procedures of the mitral valve is an infrequent but potentially life-threatening complication (1–3). Due to its close anatomical relationship to the posterior mitral valve annulus, there is a relevant risk of causing a stenosis or an occlusion of the left circumflex artery, especially by surgical annular sutures. The perioperative clinical course is heterogeneous, ranging from—initially—asymptomatic or solely electrocardiographic abnormalities to cardiogenic shock. Both severely impaired ventricular contractility or malignant arrhythmia may potentially lead to a weaning failure from cardiopulmonary bypass (CPB) and eventually result in chronic heart failure with persistently reduced ejection fraction. Possible therapeutic strategies include the immediate reopening of causal sutures, aortocoronary bypass grafting or percutaneous coronary intervention (PCI), yet PCI seems to be the preferred method at present.